Tukar Tambah Kendaraan Bekas di Showroom Bijo Motor Menurut Fikih Ekonomi (Studi Kasus Shoroom Bijo Motor Batusangkar) - Abdul Rahim A; Syamsurizal Syamsurizal; Anisa Marseli (Departement of Mathematics Education, 2022)
This study discusses the trade-in of used vehicles at the bijo motor showroom according to economic fiqh. In the contemporary era, there are many transactions carried out by every institution without regard to Islamic law, but it is different from the business initiated by the owner of the bijo motor showroom. The transaction at the showroom uses a sale and purchase agreement according to sharia economic law and meets the requirements and pillars of buying and selling, thus avoiding the practice of usury. This study uses field research, namely the research results obtained through interviews and data analysis by adjusting to the forms of buying and selling that are allowed in Islam and comparing the theory of trade-in used vehicles according to economic fiqh with practice in the bijo motor showroom and analyzed by domain. The results of this study, that the practice of trade-in vehicles carried out by the bijo motor showroom located in the limo of the people, Tanah Datar Regency uses a vehicle sale and purchase agreement according to Islamic sharia. The practice of exchanging used vehicles at the bijo motor showroom uses a sale and purchase agreement for one item at a time without combining the two items they sell and buy. And if consumers buy and sell credit, the showroom directly cooperates with Bank Syariah Indonesia (BSI).